Protecting a Client’s Confidences: Recent Developments in Privileged Communication Between Attorneys and Accountants - Barsky, Noah P.; Catanach, Anthony H.; Lipin, Ilya A.; Rhoades-Catanach, Shelley C. (Journal of Law and Commerce, 2010)
The attorney-client privilege is one of the foundations of our jurisprudence. Originally, designed to prevent attorneys from testifying against their clients, the privilege eventually evolved to reflect legal, societal, and financial complexities. This privilege depends on full disclosure and open communication between attorney and the client in order to provide competent and adequate representation. Today, attorneys often require and rely on expert guidance of accountants for various issues pertaining to litigation and transactional work. This article illustrates how the recent cases of Commissioner v. Comcast Corp. and United States v. Textron affect privileged communications in complex tax and transactional matters between attorneys and accountants retained for the purposes of client representation. The article also offers guidance on how to preserve privilege in communication between attorneys and accountants as waiver of such privilege may have significant and costly implications. At conclusion, unresolved issues pertaining to privileged communication are discussed and solutions are offered.